16SrRNA sequencing analysis of rat intestinal microbiota. - Yingying Chen (500738) (2025)
(A) Species enrichment at the phylum level; (B) Species enrichment at the genus level; (C) Analysis of microbial α-diversity index; (D) Analysis of microbial β-diversity index; (E) Venn diagram of sample ASV/OUT; (F) ASV/OTU abundance histograms in different regions of the Venn diagram at the genus level; (G) Heat map of species composition at the genus level with species clustering. n = 6. *P < 0.05, **P < 0.01.